2019
DOI: 10.1371/journal.pone.0218155
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between clinical and pathological features of cutaneous calciphylaxis

Abstract: Calciphylaxis is a rare and life-threatening disease that classically manifests with painful skin lesions. It occurs mainly in patients with end-stage renal disease (ESRD) treated with dialysis, has poor outcomes, and has no FDA-approved treatment. Our cohort study aims to examine the clinical and pathological features of calciphylaxis and investigates the correlation between cutaneous clinical manifestations and histopathological findings. Data from 70 calciphylaxis patients who were evaluated at the Massachu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…24 Furthermore, subsequent microvascular thrombosis may explain the characteristic exquisitely tender nature of calciphylaxis as the presence of fibrin thrombi in skin biopsies has been associated with clinical pain severity. 25 Aberrations in molecular mediators that normally inhibit microvascular calcification have been implicated in the pathogenesis of calciphylaxis. For example, carboxylated matrix G1a protein (MGP) is an extracellular matrix peptide produced by vascular and endothelial cells that directly inhibits calcification.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…24 Furthermore, subsequent microvascular thrombosis may explain the characteristic exquisitely tender nature of calciphylaxis as the presence of fibrin thrombi in skin biopsies has been associated with clinical pain severity. 25 Aberrations in molecular mediators that normally inhibit microvascular calcification have been implicated in the pathogenesis of calciphylaxis. For example, carboxylated matrix G1a protein (MGP) is an extracellular matrix peptide produced by vascular and endothelial cells that directly inhibits calcification.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…23 The role of vitamin K as a calcification inhibitor is supported by the observation that even in the absence of warfarin, vitamin K deficiency is found in 80% of patients with CUA. 22,23 However, it cannot be ignored that the hypercoagulable conditions for which warfarin is prescribed may also play a role as other reports have identified an association between an increased propensity for thromboses and increased predisposition for CUA. 24,25 In addition, we also found that sevelamer therapy was associated with higher odds of developing CUA which has not been previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…Initial biopsy from an outside institution revealed fibrin thrombi with no evidence of calcification. Fibrin thrombi are seen in almost half of biopsies for calciphylaxis, and this histological finding is associated with pain severity 5. Due to the appearance of the rash, consideration of the patient’s comorbidities and initial biopsy results differential diagnosis included cutaneous manifestation of known CMV infection, cryoglobulinaemic vasculitis with history of hepatitis C, disseminated intravascular coagulopathy or atypical presentation of COVID-19 infection considering her rash occurred at the onset of the pandemic and little was known about the disease with COVID-19 vaccinations unavailable at initial presentation.…”
Section: Discussionmentioning
confidence: 99%